The Perfect SalesForce - Gatehouse, Derek (Ascent Audio, 2017)
How any company can build an incredibly effective salesforce by learning from the best in the world Despite billions spent every year on personality profiling, sales training, motivational experts, coaches, and incentives, there's never been a proven formula for building a salesforce of top performers. Finding such a "holy grail" of sales has been Derek Gatehouse's obsession for decades. To identify what makes a top-producing salesperson-the kind who sells four times more than everyone else-and why some sales teams have a high percentage of top producers, he interviewed more than two thousand executives in many different industries. His findings challenge the conventional wisdom about hiring, training, managing, and rewarding a sales team. Gatehouse has tested virtually every personality assessment tool, sales process, training methodology, and management system available, only to conclude that the vast majority of those systems don't raise performance in a lasting way. Instead, the world's greatest sales teams share six simple but critical practices. For instance, they all: Hire for talent, not skill or even experience Blend positive and negative motivators Measure results instead of micromanaging process The audiobook features dozens of anecdotes and clear lessons for any company seeking dramatic improvement in its sales performance.